Changing approaches to interactive marketing communications due to the development of 5G technology - L. G. Akhmaeva (Цифровая социология)
The process of changing approaches to interactive marketing communications, due to the development of 5G technology – high-speed data transmission over 5G wireless networks has been reviewed. The main facts about 5G technology have been given, the impact of its introduction on consumer behavior, the penetration of augmented and virtual reality technologies into everyday life and the change in the format of marketing communications in the following areas have been considered: retail and delivery of goods, virtual spaces for work and business, mobile cloud gaming and streaming, art, street traffic and parking, public transport, pedestrian and bicycle traffic, weather conditions and energy supply.The key directions of development of interactive marketing communications with the arrival of 5G have been considered: delivery of messages to any place and at any time, an increase in the number of connected devices, instant feedback, new formats and media.Conclusions have been drawn regarding the changes in interactive marketing communications: due to the ultra-high speeds of 5G, the loading time of the commercial will be significantly reduced, which will significantly improve the consumer experience at the level of using devices and applications. The same factor will affect the growth of mobile traffic, and, consequently, advertisers will have to think through advertising integrations more efficiently, adapting them for mobile devices and trying to make them more personalised. And the most obvious technology that will gain a large market share with the spread of 5G is augmented technology, which will become not just part of an unusual user experience, but a full-fledged and effective advertising campaign tool. Video content will gain an undisputed leadership among other types of content in the advertising market. Targeting and personalisation of content will become even more accurate and simpler, advertising offers to potential buyers will be more personalised, it is also supposed to transform advertising formats for audio messages and integrate voice assistants into various devices.